A study on factors influencing the effectiveness of information content in newspaper advertising in promoting government's new policy: Goods and services tax (GST) / Mardzuki Madzlan - Madzlan, Mardzuki (Institute of Graduate Studies, UiTM, 2018)
In the information management field, disseminating information is one of the critical factors in ensuring efficient information transferring between one point to another. It is an act to establish communication by sender in the act to share information to the receiver in an attempt to equip the receiver with new and useful information and also to inform an individual and a group of individual on information that is will give them interest. For the Government of Malaysia, it is a form of communication and important part in informing the public through mass media. One way that is often used by the government is the use of advertising as a tool to achieve specific goals through communication in transferring information to the public. It also used to create awareness and educate public on certain issues and also to introduce new policy and initiatives through a series of campaign using advertising. It provides an effective output using advertising strength in persuading the audience and its capability to enforce attitude change. Dissemination of information is an important issue to address among agencies in Malaysia, and as part of information management field and the new information society in the 20th century, information is an essential commodity and regarded as valuable in every sector and industry which gives organization advantages in every front. Advertising is a tool used to deliver information in most fashioned and interesting ways. It disseminates information using various mediums and this research focuses newspaper as a medium to disseminate information through newspaper advertisement…